Political campaigns on YouTube: trade unions' mobilisation in Europe. (17th December 2020) - Uba, Katrin; Jansson, Jenny
Abstract : Trade unions are called to increase their influence on policy‐making by becoming more politically active and use social media, but only a few studies investigate unions' online political activism. We propose that industrial relations regime of a country relates to unions' perceived opportunities for mobilisation and thereby also unions' online political activism. We test this argument with the help of data about European trade union confederations' political mobilisation on YouTube, 2007–2017. The results showed, expectedly, that resource‐rich confederations in the organised corporatist regime (Scandinavia) use YouTube for political activism to lesser degree than in other regimes; when these confederations do pursue political activism, such videos are often related to elections and reflect the political party‐union relationship. Unexpectedly, the resource‐poor confederations in the transitional regime (Central and Eastern Europe) mobilised politically on YouTube to the same extent as have the confederations in the social partnership, liberal and state‐centred regimes.